Multi-function Hybrid Microgrid with Four-Leg Voltage Source Inverter - da Silva, José Francisco Resende; Baquero, John Freddy Franco; Ferreira, Fabio de Oliveira; Miranda, Hugo Villela de; Pereira, Thobias Antônio Cândido; Rodrigues, Marcos Paulo Gonçalves; Nielson, Rafael (International Journal of Advanced Engineering Research and Science, 2020)
Unintentional islanding of distributed generation systems is generally avoided as a safety measure implied by worldwide electrical standards. Considering current grid technologies with better sensing capabilities and semiconductor devices with novel capabilities that allow faster response times and higher maximum ratings, there are some applications where distributed resources could improve reliability in the case of intentional islanding. Safe microgrid equipment with better isolation and control features allows efficient use of energy surplus whenever grid fault events occur, feeding emergency energy to critical loads. In this context, a 20 kW hybrid on-grid/off-grid multi-function microgridis presented along with a simplified approach for designing the contained power inverter used with intentional islanding function.